Dragonbreath : attack of the ninja frogs - Vernon, Ursula (New York, NY : Dial Books, 2010)
When Suki the salamander--the new foreign exchange student--is being stalked by ninja frogs, Danny, Wendell the iguana, and Suki travel to Great-grandfather Dragonbreath's home in mythical Japan to find a solution for the problem.
A Junior Library Guild selection
Keywords: Ninja -- Juvenile fiction; Dragons -- Juvenile fiction; Reptiles -- Juvenile fiction; Amphibians -- Juvenile fiction; Friendship -- Juvenile fiction; Japan -- Juvenile fiction; Ninja -- Fiction; Dragons -- Fiction; Reptiles -- Fiction; Amphibians -- Fiction; Friendship -- Fiction; Japan -- Fiction